2022
DOI: 10.3389/fpubh.2022.868416
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Education Level With Survival Outcomes and Treatment Receipt in Patients With Gastric Adenocarcinoma

Abstract: BackgroundIt remains largely unclear how education level, an important socioeconomic factor, affects prognoses for patients with gastric adenocarcinoma (GAC). We aimed to demonstrate the associations between education level and clinical outcomes in patients with GAC.MethodsWe included a total of 30,409 patients diagnosed with GAC from the Surveillance, Epidemiology, and End Results 18 registry database. Education level, household income, unemployment rate, poverty rate, insurance status, and marital status wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
(44 reference statements)
1
1
0
Order By: Relevance
“…This research also indicated that educational level was closely related to the prognosis of recipients, which might be inseparable from the post-transplant nursing care of patients. We observed a similar phenomenon in other diseases, where highly educated patients with gastric cancer and those who underwent knee surgery had better outcomes than those with low levels of education ( 15 , 16 ). A better educational background can help patients understand basic health information related to their disease, resulting in better adherence to immunosuppressive drugs after kidney transplantation.…”
Section: Discussionsupporting
confidence: 74%
“…This research also indicated that educational level was closely related to the prognosis of recipients, which might be inseparable from the post-transplant nursing care of patients. We observed a similar phenomenon in other diseases, where highly educated patients with gastric cancer and those who underwent knee surgery had better outcomes than those with low levels of education ( 15 , 16 ). A better educational background can help patients understand basic health information related to their disease, resulting in better adherence to immunosuppressive drugs after kidney transplantation.…”
Section: Discussionsupporting
confidence: 74%
“…These factors collectively contribute to a more favorable health outcome. 42 , 43 , 44 Therefore, it is suggested that clinical practitioners should pay attention to patients with low education level and provide more tailored support where necessary.…”
Section: Discussionmentioning
confidence: 99%